2022
DOI: 10.3390/nu14071376
|View full text |Cite
|
Sign up to set email alerts
|

Diet, Fecal Microbiome, and Trimethylamine N-Oxide in a Cohort of Metabolically Healthy United States Adults

Abstract: TMAO is elevated in individuals with cardiometabolic diseases, but it is unknown whether the metabolite is a biomarker of concern in healthy individuals. We conducted a cross-sectional study in metabolically healthy adults aged 18–66 years with BMI 18–44 kg/m2 and assessed the relationship between TMAO and diet, the fecal microbiome, and cardiometabolic risk factors. TMAO was measured in fasted plasma samples by liquid chromatography mass spectrometry. The fecal microbiome was assessed by 16S ribosomal RNA seq… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
9
0
4

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(24 citation statements)
references
References 48 publications
3
9
0
4
Order By: Relevance
“…9, 21, 55 Taken together with our results, these findings suggest that circulating TMAO may not be a metabolite of concern in individuals from the general population. 9, 17, 21, 55…”
Section: Discussionsupporting
confidence: 81%
See 2 more Smart Citations
“…9, 21, 55 Taken together with our results, these findings suggest that circulating TMAO may not be a metabolite of concern in individuals from the general population. 9, 17, 21, 55…”
Section: Discussionsupporting
confidence: 81%
“…14, 15, 16, 74 In our study population, no association was found between TMAO and eggs or red meat. 21 Fish and seafood are rich in TMAO and TMA and they can be directly absorbed without being transformed by gut microbiota. 14 As previous studies linked TMAO to atherosclerosis and CVD, these findings might be contra intuitive as fish is generally accepted to be cardioprotective.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Определены бактерии, синтезирующие ТМАО: тип Firmicutes (роды Anaerococcus, Clostridium, Enterococcus, Streptococcus, Desulfovibrio, Eubacterium), тип Proteobacteria (Enterobacter, Escherichia, Klebsiella, Proteus, Actinobacter, Citrobacter), тип Actinobacteria (Mobiluncus, Olsenella) и тип Bacteroidetes (Bacteroides) [16,27]. Напротив, у метаболически здоровых взрослых первый терциль концентрации ТМАО в плазме крови натощак был обогащен родами Roseburia, Butyrivibrio, Coprobacillus и Catenibacterium по сравнению с третьим терцилем [30]. Firmicutes, как правило, содержат ТМА-генерирующий кластер генов, утилизирующих холин [16], что идентифицировали метагеномные скрининги [30].…”
Section: микробная экология при атеросклерозеunclassified
“…Напротив, у метаболически здоровых взрослых первый терциль концентрации ТМАО в плазме крови натощак был обогащен родами Roseburia, Butyrivibrio, Coprobacillus и Catenibacterium по сравнению с третьим терцилем [30]. Firmicutes, как правило, содержат ТМА-генерирующий кластер генов, утилизирующих холин [16], что идентифицировали метагеномные скрининги [30].…”
Section: микробная экология при атеросклерозеunclassified